The Dynamic Analysis of Non-State Actor Involvement in Post-Disaster Management: A Case Study of Cold Lava Floods in Nagari Bukik Batabuah, Agam Regency - Vanny, Dasti; Frinaldi, Aldri (Faculty of Social Science, Universitas Negeri Padang, 2025)
Post-disaster management in Indonesia faces significant challenges, particularly in highly vulnerable areas such as Nagari Bukik Batabuah, Agam Regency, which was affected by cold lava floods from the eruption of Mount Marapi in May 2024. The main problem lies in collaboration between the government and Non-State Actors (NSAs), particularly regarding differences in recovery approaches, obstacles to data collection on vulnerable groups, and obstacles in aid distribution. This study aims to analyze the dynamics of NSA involvement in post-disaster management, identify patterns of cross-actor interaction, and challenges faced in the collaborative process. Using qualitative methods with a descriptive approach, this study collected data through observation, interviews, and documentation analyzed using the Manual Data Analysis Procedure (MDAP) and Strauss and Corbin coding techniques. The research findings reveal that NSAs, such as Jemari Sakato, play a significant role in accelerating recovery through inclusive programs and assistance targeting vulnerable groups. However, collaboration with the village government is often hampered by weak coordination, lack of data transparency, and suboptimal collaborative institutional design. Public response to the NSA intervention was generally positive, but criticisms persisted regarding data collection and information transparency. This study emphasizes the need to strengthen collaborative governance that is inclusive, participatory, and equitable so that post-disaster recovery in vulnerable areas can be effective, sustainable, and responsive to local needs.